Elucidating the Factors Limiting the Photovoltaic Performance of Mixed Sb–Bi Halide Elpasolite Absorbers. Issue 11 (29th September 2022) - Li, Zewei; Huang, Yi-Teng; Mohan, Lokeshwari; Zelewski, Szymon J.; Friend, Richard H.; Briscoe, Joe; Hoye, Robert L. Z.
Abstract : Although Cs2 AgBiBr6 halide elpasolites have gained substantial attention as potential nontoxic and stable alternatives to lead–halide perovskites, they are limited by their wide bandgaps >2.2 eV. Alloying with Sb into the pnictogen site has been shown to be an effective method to lower the bandgap, but this has not translated into improvements in photovoltaic (PV) performance. Herein, the underlying causes are investigated. Pinhole‐free films of Cs2 Ag(Sb x Bi1− x )Br6 are achieved through antisolvent dripping, but PV devices still exhibit a reduction in power conversion efficiency from 0.44% ± 0.02% (without Sb) to 0.073% ± 0.007% (90% Sb; lowest bandgap). There is a 0.7 V reduction in the open‐circuit voltage, which correlates with the appearance of a sub‐bandgap state ≈0.7 eV below the optical bandgap in the Sb‐containing elpasolite films, as found in both absorbance and photoluminescence measurements. Through detailed Williamson–Hall analysis, it is found that adding Sb into the elpasolite films leads to an increase in film strain. This strain is relieved through aerosol‐assisted solvent treatment, which reduces both the sub‐bandgap state density and energetic disorder in the films, as well as reducing the fast early decay in the photogenerated carrier population due to trap filling. This work shows that Sb alloying leads to the introduction of extra sub‐bandgap states that limit the PV performance, but can be mitigated through post‐annealing treatment to reduce disorder and strain. Abstract : Sb‐alloying has been proposed as a strategy to improve the visible light absorption of Cs2 AgBiBr6 elpasolites by reducing the bandgap, but this approach has not so far led to improvements in photovoltaic performance. Herein, it is shown that this is due to the introduction of a sub‐bandgap loss channel, which may arise from an increase in film strain.